2016
DOI: 10.1016/j.trci.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Poor cerebrovascular function is an early marker of cognitive decline in healthy postmenopausal women

Abstract: IntroductionImpairment of cerebrovascular function becomes evident after menopause. No study has yet explored relationships between deficits in cerebrovascular function, cognitive performance, and mood in postmenopausal women.MethodCerebrovascular function was assessed in 80 healthy postmenopausal women by monitoring blood flow velocity (BFV) in the middle and posterior cerebral arteries using transcranial Doppler ultrasound at rest, following a hypercapnic challenge, and during performance of a cognitive test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Neuronal activation promotes the endothelium to release nitric oxide, resulting in the dilatation of local arterioles, which is reflected in increased blood flow in larger vessels (neurovascular coupling). Impaired vasodilation may reduce the normal perfusion increase during neuronal activation potentially contributing to poor cognitive performance in patients with congenital heart disease; in healthy older women, early deficits in cerebral blood responses predicted cognitive dysfunction, with altered neurovascular coupling associated with cognitive deficits in patients with diabetes mellitus . Impaired cerebral blood flow response to cognitive stimulus has also been associated with abnormal gait patterns, in keeping with differences in gait speed observed between the two cohorts .…”
Section: Discussionmentioning
confidence: 71%
“…Neuronal activation promotes the endothelium to release nitric oxide, resulting in the dilatation of local arterioles, which is reflected in increased blood flow in larger vessels (neurovascular coupling). Impaired vasodilation may reduce the normal perfusion increase during neuronal activation potentially contributing to poor cognitive performance in patients with congenital heart disease; in healthy older women, early deficits in cerebral blood responses predicted cognitive dysfunction, with altered neurovascular coupling associated with cognitive deficits in patients with diabetes mellitus . Impaired cerebral blood flow response to cognitive stimulus has also been associated with abnormal gait patterns, in keeping with differences in gait speed observed between the two cohorts .…”
Section: Discussionmentioning
confidence: 71%
“…Similarly, Wong et al . also found acute enhancement of CVR to hypercapnia and in neurovascular coupling capacity in older adults with type 2 diabetes . Both authors provided the key evidence of the vasorelaxatory properties of resveratrol in humans, which could be attributed to an interaction with aspects of NO synthesis .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, estrogen decline at menopause can have severe repercussions on the vasculature. Recently, a cross‐sectional study found that impaired cerebrovascular function, particularly CVR to cognitive tests (neurovascular coupling capacity) and cerebral artery stiffness, correlated with poor cognitive performance in healthy postmenopausal women not taking HRT . This observation highlights the importance of preventative strategies to attenuate premature cognitive decline.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of early cerebrovascular dysfunction has important diagnostic implications for future cognitive decline [36]. We have previously shown that poor cerebrovascular function is predictive of cognitive decline in healthy postmenopausal women [8].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced cerebral blood flow (CBF) and CVR are associated with cognitive impairment [7]. We have also reported that reduced CVR during mental task activation (neurovascular coupling) is predictive of poor cognitive performance in postmenopausal women [8]. A meta-analysis has shown that postmenopausal women perform worse on verbal memory and executive function tests compared to peri-menopausal women [9].…”
Section: Introductionmentioning
confidence: 99%